Respuesta :

Answer:

[tex]f(x)=(x-5)^{2}+19[/tex]

Step-by-step explanation:

we have

[tex]f(x)=x^{2}-10x+44[/tex]

Group terms that contain the same variable, and move the constant to the opposite side of the equation

[tex]f(x)-44=x^{2}-10x[/tex]

Complete the square. Remember to balance the equation by adding the same constants to each side.

[tex]f(x)-44+25=x^{2}-10x+25[/tex]

[tex]f(x)-19=x^{2}-10x+25[/tex]

Rewrite as perfect squares

[tex]f(x)-19=(x-5)^{2}[/tex]

[tex]f(x)=(x-5)^{2}+19[/tex]